The Colony: conceptualising space through the corporate culture, work, and quotidian life of an Indian corporation in Tete, Mozambique - Barnard, Melinda (My University, 2016)
As capitalism speeds up and spreads out whilst entering a new phase of internationalization, individuals are left with uncertainty with regards to what ‘place’ means and how they should relate to it. Within the corporate sphere, this must ring true for many office workers – especially those who have migrated to new cities or countries. Scholarly work on time-space compression has prompted anthropologists (and social theorists) to re-think ‘place’ not solely in terms of capital, but also in relation to race or gender. By looking at an Indian-owned international mining corporation, which has entered Africa – specifically in Tete, Mozambique – with, in their view, the aim of functioning as a ‘local company’, I wish to interrogate corporate self-conceptualisation by asking the question: “What does it mean to be an Indian corporation in Africa?” I explore their Colony – made up of the corporate administrative office and adjacent housing compound – by looking at how this space is constructed in relation to the outside space of the country in which it is located, as well as through an unpacking of this construction with regards to workplace relations in the corporate office and in the lives of office workers both within and outside of the office. We can no longer look at a single place without considering the complex mix of the global that makes it up, that indeed collapses into it. We are challenged to see place as a point of intersection; to not merely look at the visible networks of global capital, but also to recognise and give importance to those invisible flows of people and networks that link them, especially in relation to south-south partnerships and interactions. When looking at the office space, we must acknowledge that the office space is more than simply a daily meeting place – it is not static, and it has no boundaries (other than its four walls). Rather, it is more complex than a single identity and yet, at the same time, is unique in the complexities that unify it.
Submitted in partial fulfilment of the requirements of a Masters of arts by coursework and research report in social anthropology University of the Witwatersrand, Johannesburg
Keywords: Business anthropology--Mozambique; Corporate culture--Mozambique